Maturity-Onset Diabetes of Young Type 5: Diabetes with Extrapancreatic Features - Adnan Haider; Oksana Symczyk; Ayesha Hassan; Muhammad Atif Khan; Inderpreet Madahar; Dylan Holland (Case Reports in Endocrinology)
Objective. This case involves a new-onset diabetes patient diagnosed during pregnancy with the congenital dysplastic right kidney. Case Report. Clinical presentation, biochemical features, imaging in a patient with diabetes diagnosed during pregnancy, and congenital dysplastic right kidney. Discussion. We present a case of a 22-year-old female with the congenital dysplastic right kidney diagnosed with gestational diabetes mellitus after failing a 1-hour oral glucose tolerance test, requiring insulin during pregnancy. Because of the family history of diabetes and morphologic renal abnormalities at young ages on the maternal side of the family, our patient was evaluated for maturity-onset diabetes of adult and was found to have HNF-1β mutation. Conclusion. This case highlights the importance of considering the diagnosis of maturity-onset diabetes of young and particularly MODY-5 in individuals with extrapancreatic features. MODY-5 should also be considered in a patient undergoing renal transplant at young ages with a family history of morphologic renal abnormalities.